THE SIGNIFICANCE OF CIRCULATING IMMUNE COMPLEXES AS PROINFLAMMATORY MARKERS IN CHILDREN WITH EPIDERMOLYSIS BULLOSA (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Systemic inflammation is a well-recognized aspect of epidermolysis bullosa (EB), yet many of the underlying immune mechanisms remain under active investigation. The aim of this study was to evaluate the diagnostic and prognostic significance of circulating immune complexes (CICs) of different molecular sizes in pediatric patients with EB.